2020
DOI: 10.1002/cpdd.898
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 Study of the Effects of the Tuberculosis Treatment Pretomanid, Alone and in Combination With Moxifloxacin, on the QTc Interval in Healthy Volunteers

Abstract: Tuberculosis (TB) continues to be a serious threat to public health throughout the world. Newer treatments are needed that could offer simplified regimens with activity against both drug-sensitive and drug-resistant bacilli, while optimizing safety. Pretomanid (PA-824), a nitroimidazooxazine compound, is a new drug for the treatment of pulmonary TB that was recently approved in the United States and Europe in the context of a regimen combined with bedaquiline and linezolid. This phase 1 double-blind, randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
1
2
0
1
Order By: Relevance
“…In general, these ndings in a Chinese population were comparable to previous ndings of Phase I studies in non-Chinese populations. [8][9][10][11][12][13] Most of the AEs observed in this trial were reported in previously published studies of pretomanid and, overall, the safety pro le of pretomanid in this trial was consistent with previous ndings. [8-16, 18] In a pooled analysis of TEAEs in non-Chinese subjects who received pretomanid in prior phase 1 studies (single or multiple doses), the most common TEAEs by system organ class were nervous system disorders (37.7%), gastrointestinal disorders (24.2%), and investigations (21.8%).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In general, these ndings in a Chinese population were comparable to previous ndings of Phase I studies in non-Chinese populations. [8][9][10][11][12][13] Most of the AEs observed in this trial were reported in previously published studies of pretomanid and, overall, the safety pro le of pretomanid in this trial was consistent with previous ndings. [8-16, 18] In a pooled analysis of TEAEs in non-Chinese subjects who received pretomanid in prior phase 1 studies (single or multiple doses), the most common TEAEs by system organ class were nervous system disorders (37.7%), gastrointestinal disorders (24.2%), and investigations (21.8%).…”
Section: Discussionsupporting
confidence: 88%
“…[7] Results from a total of eight phase I trials of single and repeated administration of pretomanid have been published (CL-001, CL-002, CL-003, CL-005, CL-006, CL-009, A5306 and DMID 10-0058), including a total of 289 healthy participants. [8][9][10][11][12][13] These previous studies investigated single doses of pretomanid ranging from 50 to 1500 mg and repeated doses ranging from 200 to 1000 mg/day from 7 to 14 days. Furthermore, the PK pro le of pretomanid was also investigated in two phase IIa studies (CL-007 and CL-010) of pretomanid conducted in tuberculosis patients.…”
Section: Introductionmentioning
confidence: 99%
“…In Phase I studies in healthy patients, no cardiovascular-related effects on 2-lead cardiac profiles or 12-lead ECG parameters, including heart rate and QT interval, were noted after single doses of pretomanid up to 1500 mg or seven repeat doses up to 600 mg [16] . In a randomized, double-blind, placebo- and positive controlled, crossover, thorough QT study of pretomanid, single doses of pretomanid up to 1000 mg caused no QTc prolongation of clinical concern in healthy subjects [17] . Pretomanid monotherapy during two early bactericidal activity (EBA) studies up to 1200 mg for 14 days was well tolerated with no clinically significant QTc changes [18] , [19] .…”
Section: Discussionmentioning
confidence: 97%
“…Li и соавт. [85] изучили влияние монотерапии Ра (400 и 1000 мг) и комбинации Ра (400 мг) с Mfx (400 мг) на интервал QTc у 74 субъектов. Моксифлоксацин не влиял на фармакокинетику Ра, а действие комбинации препаратов соответствовало эффекту одного Mfx.…”
Section: нитроимидазолыunclassified